Asset Specificity On Conditional Conservatism - Ahmad Waluya Jati; Mohammad Naufal; Ike Arisanti; Dhaniel Syam (Jurnal Reviu Akuntansi dan Keuangan, 2021)
Asset specificity, an asset creates company’s distinctive competency that tough to be imitated by competitor. Howere asset specificity features a direct impact on a firm’s in progress truthful price determination, bankruptcy risk, liquidation value, and abandonment option. On alternative hand, the ownerhip of this quality specificity has serious consequences on finance strategy. Bank faces serious issue to create a correct valuation of specific and opaque asset so bank charges higher value of debt. we discover no distinction within the extent to that good news is delayed in earnings for corporations conditional on asset specificity. This study use 280 non finance service and non agriculture  type listed in IDX on 2018. However The information assortment used documentation technique and also the data analysis utilized was multiple correlation analysis. we have a tendency to document a significant negative association between quality specificity and conditional conservatism especially in Mining, Miscellaneous industry, and good consumer Industry But we notice new findings within the infrastructure sector there's a significant positive impact of specificity Asset specificity on conservatism.